Pharmacological Intensification of the Process of Water Dissociation, or Human Photosynthesis, and Its Impact on the Recovery Mechanisms of Diverse Etiology in Tissues Affected by Bloodshed - Arturo Solís Herrera; María del Carmen Arias Esparza; J. Jesús Alvarado Esquivel; Graciela Landín Miranda; Ruth Isabel Solís Arias; Paola Eugenia Solís Arias; Martha Patricia Solís Arias (Highlights on Medicine and Medical Research Vol. 9, 2021)
The human retina’s photoreceptor layer has some unique features. Their energy requirements are the highest in the organism; in proportion, rods and cones require 10-fold the energy consumed by the cerebral cortex, 6-fold more than the cardiac muscle, and 3-fold more than the renal cortex. Surprisingly, there are no blood vessels in the photoreceptor layer. So, where is the energy to this tissue coming from? In this article we will describe the hitherto unknown explanation. Human photosynthesis is the origin of life and it’s placed at first in the sequence of all biochemical processes of life; any other function or reaction it’s secondary to water dissociation and directly or indirectly are depending on the energy released by our hitherto unknown human photo-system.